Hyperkalemia-induced brugada phenocopy: A rare electrocardiogram manifestation - Satyajit Singh; Chandra Prakash Thakur; Surendra Naik; Muneshwar Kumar (Journal of the Practice of Cardiovascular Sciences, 2022)
Hyperkalemia-induced Brugada ECG pattern is rare. Although the association of hyperkalemia with Brugada pattern is a known entity, it is also very important to be aware of this presentation as the treatment of this Brugada Phenocopy is different from Brugada syndrome . This case presented with a Brugada like ECG but had hyperkalemia. On correcting the hyperkalemia, the ECG settled to normal.